Eksistensi peserta pelatihan kerja program pemagangan ilegal luar negeri khususnya di Jepang - Bilqis Fani Fani Zulfakanti; Agus Mulya Karsona; Holyness Singadimedja (University of Merdeka Malang, 2021)
Intern training program outside Indonesia region as a form of manpower development has significant role to overcome the high unemployment rate in Indonesia. In its implementation, the problem occurs wgen the participant of intern training program run away from the program or used to be called as illegal intern trainee. This paper aims to know and understand the existence of illegal intern trainee including the impacts, as well as legal actions that can be taken by Indonesia government to overcome the problems. This study is based on normative juridical approach with primary and secondary data sources. The study shows that the existence of illegal intern trainee that violate Indonesia’s and accepting country’s regulations causes loss of rights of the participant as intern trainee. As a consequence, ocupational safety facilities, and insurance assistance in the case of work accident, illness, nor mortality can not be accomodated, nonetheless assistance can still be given in the context of the illegal intern trainee status as Indonesian citizen. The Ministry of Manpower of the Republic of Indonesia can take preventif actions in the form of supervision and development and represive legal action by temporary revocate the sending organization’s license. In the other hand, the Ministry of Foreign Affairs of the Republic of Indonesia can take represive legal actions in the form of legal assistance, aid, including return assistance.How to Cite Item: Zulfakanti, B., Karsona, A., Singadimedja, H. (2021). Eksistensi peserta pelatihan kerja program pemagangan ilegal luar negeri khususnya di Jepang. Jurnal Cakrawala Hukum, 12(2), 139-149. doi:https://doi.org/10.26905/idjch.v12i2.4830